Improving food production in Nigeria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Strategy for agricultural development in Nigeria: focus on Rivers State edited by N O Isirimah, A Monsi, and P D S Kinako 172pp 1989 ISBN 978 2801 01 1 Belk Publishers, 13 Kolo Street Diobu, Port Harcourt, Rivers State NIGERIA